2017
DOI: 10.1016/j.jacr.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Educational Impact of a Structured Radiation Oncology Clerkship Curriculum: An Interinstitutional Comparison

Abstract: Purpose Many medical school clerkships have structured curricula, however most radiation oncology clerkships do not. The Radiation Oncology Education Collaborative Group (ROECSG) implemented a curriculum for fourth-year radiation oncology clerkships at 14 institutions. We hypothesized that students completing clerkships with the curriculum would report greater subjective knowledge and comfort to function as a radiation oncology resident compared with students completing clerkships without the curriculum. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…For phase 2, a total of 220 applicants to the University of Chicago/University of Illinois at Chicago radiation oncology residency program were invited to complete the 2017 annual clerkship experience survey (7, 8, 19). A total of 77 complete responses were returned for a response rate of 35.0%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For phase 2, a total of 220 applicants to the University of Chicago/University of Illinois at Chicago radiation oncology residency program were invited to complete the 2017 annual clerkship experience survey (7, 8, 19). A total of 77 complete responses were returned for a response rate of 35.0%.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional radiation oncology medical student clerkship is an audition elective (23), with a majority of students reporting limited didactic education (7, 8, 19). Although prior studies have shown an improvement in students’ subjective perceptions of preparedness for residency training (8) and subjective radiation oncology knowledge (19), this study demonstrates improved short-and long-term objective knowledge of radiation oncology topics. These results suggest that a structured didactic curriculum should be a standard component of any radiation oncology clerkship elective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multidisciplinary cancer management ("tumor board") conferences are common at academic centers but are infrequently used for the purpose of teaching medical students, although they would expose students to a real-world collaborative process among physicians and give perspective on the multidisciplinary aspects of clinical oncology, experiences that are often lacking in US and Canadian medical curricula. [1][2][3][4] Such an activity may also be particularly valuable to radiation oncologists, given the relative dearth of other opportunities to expose the average student to radiation oncology in most curricula [2][3][4][5] and the American Society for Radiation Oncology's goal of elevating the profile of the field 6 . However, whether a mentored "tumor board shadowing" activity that is primarily observational and lacks direct patient contact is a valuable educational activity is unclear.…”
Section: Introductionmentioning
confidence: 99%